Technology and Teacher Education in Canada - Mohammed Estaiteyeh; Megan Cotnam-Kappel; Norman Vaughan (The Canadian Network for Innovation in Education (CNIE), 2024)
Technology and Teacher Education is part of the Canadian Association of Teacher Education (CATE), a constituent of the Canadian Society for the Study of Education (CSSE). Its mission is to foster a collaborative network of educational researchers dedicated to exploring the intersections of technology and teacher education in Canada. Aligning with this mission, this special issue showcases Canadian scholar expertise and amplifies the diverse voices of the TATE community. Inspired by discussions held during our annual TATE conference, where we focused on lessons learned from emergency remote teaching during the COVID-19 pandemic and the rapid technological advancements that teacher education programs are navigating, this issue offers a collection of studies from Canadian researchers working to make teaching and learning with digital technologies more effective, inclusive, and equitable for all Canadians.